A comparison of coupled microeconomic and mental health devastating alterations between low-income and affluent countries afflicted with COVID-19. - Chu, Xinxin (Work, 2021)
BACKGROUND: The exponential increase in the rate of individuals' affliction by SARS-CoV-2 (COVID-19) has put extreme strains on health care systems worldwide and has sparked fears of an impending economic recession and mental turmoil. OBJECTIVE: The review discusses the impact of COVID-19 on medical crises in two sections, focusing on the evidence presented from both neuropathological and epidemiological perspectives. First, this paper outlines how countries have implemented containment and appraises its effect on the microeconomy. Second, it highlights how government support for the economic crisis caused by COVID-19 depends on the size of a country's economy. Third, it attempts to explain how COVID-19 has affected business by explicitly evaluating each industry divided into primary, secondary, and tertiary sectors. Finally, we assert an extended discussion on the challenges and post-pandemic outlook. METHODS: Peer-reviewed studies from inception until 2021 were searched in the Google scholar, PubMed, and Scopus databases. RESULTS: Through the imposition of restrictions and lockdown measures to contain the COVID-19 pandemic spread, besides arising a broad array of mental health concerns, a drastic drop in liquidity and significant spillover effect across almost all the global economic system has ensued. CONCLUSION: The COVID-19 implication on socioeconomic issues and mental wellbeing, as the most devastating sequelae of the current pandemic, is of great importance to curb the infection and deprive post-pandemic sequelae, demanding prompt actions.